2018
DOI: 10.1038/s41467-018-07724-7
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffusion along metal/ceramic interfaces

Abstract: Interface diffusion along a metal/ceramic interface present in numerous energy and electronic devices can critically affect their performance and stability. Hole formation in a polycrystalline Ni film on an α-Al2O3 substrate coupled with a continuum diffusion analysis demonstrates that Ni diffusion along the Ni/α-Al2O3 interface is surprisingly fast. Ab initio calculations demonstrate that both Ni vacancy formation and migration energies at the coherent Ni/α-Al2O3 interface are much smaller than in bulk Ni, su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 68 publications
2
33
0
Order By: Relevance
“…Similar findings have been obtained in several other experiments [18,[21][22][23][24][25][26][27], and they have usually been attributed to PMMA residues from the fabrication processes [23][24][25] or ambient adsorbates like O 2 , H 2 O [26,27]. In our work, low-temperature current annealing was performed to remove contaminants and to improve surface quality of graphene as described in reference [3]. We measured the resistance of the device as a function of the applied gate voltage V g after each annealing cycle.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Similar findings have been obtained in several other experiments [18,[21][22][23][24][25][26][27], and they have usually been attributed to PMMA residues from the fabrication processes [23][24][25] or ambient adsorbates like O 2 , H 2 O [26,27]. In our work, low-temperature current annealing was performed to remove contaminants and to improve surface quality of graphene as described in reference [3]. We measured the resistance of the device as a function of the applied gate voltage V g after each annealing cycle.…”
Section: Resultssupporting
confidence: 86%
“…Thus, the residual charge density eventually is evaluated from the electron side data as this unipolar regime is less complex. At the cross-over point, an ultra-low residual charge density of n 0 ≈ 9 × 10 8 cm −2 is obtained, which is close to that of exfoliated graphene devices [3,8,10]. Thus, the main issue for high-quality in the suspended geometry is not the source of the graphene, but the successful current annealing.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This lower limit is by five orders of magnitude lower than the respective surface diffusivity, and by about two orders of magnitude lower than the value of grain boundary self‐diffusivity at room temperature, δD b = 8.5 × 10 −28 m 3 s −1 (here D b is the self‐diffusion coefficient along the random grain boundaries in Ag at room temperature) . The fact that metal self‐diffusion along the metal–metal and metal–ceramic interfaces is close to (or slightly lower than) the appropriate grain boundary self‐diffusion coefficient, but much higher than the bulk self‐diffusion coefficient has been discussed in the literature . It should be emphasized here that the realistic estimate of interface diffusivity obtained with the aid of our model is closely related to the ultrahigh strength of the particles: these are the high stresses and their gradients which ensure realistic diffusion fluxes and deformation rates at room temperature in Ag.…”
Section: The Diffusion Modelmentioning
confidence: 86%
“…In situ AFM has proven to be avaluable techniquef or elucidating structurala nd dynamic characteristics of crystal growth mechanisms. [66][67][68] Previously,i th as been observed that struvite nucleation and growth on ab rucite, Mg(OH) 2 ,s urface occurs via ap article-mediated process suggestingadeviation from classical crystallization; [69] however,t he physicochemical properties of these particles remain elusive, as well as the exact mechanism of struvitec rystallization, whichc ould potentially involvem ultiple pathways, including classical ion/molecule addition. To gain af undamentalu nderstanding of variousm odes of growth, we used AFM to track the dynamics of growing struvite surfaces.…”
Section: Analysis Of Struvite Surface Growthmentioning
confidence: 99%